Los videojuegos y los niños peruanos: tiempo libre y procesos de socialización - María Teresa Quiroz; Ana Rosa Tealdo (Estudios sobre las Culturas Contemporáneas)
The videogames (VG) have extensively installed themselves in homes and renting places. They concem both, boys and girls, and embrace all socioeconomical levels. In spite of the powerful fascination the VG exert, Uttle research has been done. We show the outcome of our research: not only the similarities or the differences found according to the socioeconomical levels and gender, but also the relative place that VG occupy in the general frame of traditional entertainment activities.